A companion to Ezra Pound's Guide to kulchur - Araujo, Anderson (Ezra Pound Center for Literature series., 2018)
This reader companion addresses the formidable interpretive challenges Pound's Guide to Kulchur presents to the reader, providing page-by-page glosses on key terms and passages while situating Pound's allusions and references in relation to his poetry. Striking a balance between rigorous scholarly standards and readerly accessibility, the book is designed to meet the needs of the specialist while keeping the critical apparatus unobtrusive so as also to appeal to students and the general public. A long-needed resource, A Companion to Ezra Pound's Guide to Kulchur joins Carroll Terrell's landmark A Companion to The Cantos of Ezra Pound to make a lasting contribution to the growing number of editorial and critical studies on the work of one of the most influential and controversial literary figures of the twentieth century.